Design of Mathematics Module Development Based on Guided Discovery Methods to Improve Understanding of Concept of Class X SMA/MA - Larasati, Sukmana; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Mathematical concepts are very important to be mastered by students. Students who do not understand the concept of mathematics will find it difficult to understand other mathematical concepts because of the interrelated mathematical concepts. Learning with guided discovery can guide students to construct and understand mathematical concepts. One of the teaching materials that can be used to understand the concept of matter is the module. This study aims to produce products in the form of mathematics modules based on guided discovery methods to improve understanding of concepts. This study uses the Design Development type Development Study which consists of initial product design, expert review, small group and field test. Research subjects were teachers and students of class X SMA. Research instruments in the form of interview guidelines, observation guidelines, and questionnaires. Data were analyzed using the Miles Huberman model consisting of data reduction, data display and conclusion drawing. This study concludes that the module is in the practical and valid category. Research can be further developed at the filed test stage.